RETENSI DAN EFEKTIVITAS BAHAN PENGAWET EKSTRAK DAUN CENGKEH (Syzygium aromaticum) PADA KAYU DURIAN (Durio zibethinus) TERHADAP SERANGAN RAYAP TANAH (Coptotermes sp.) - Toleng, Fitriyani N.; Erniwati, Erniwati; Ariyanti, Ariyanti (Warta Rimba, 2014)
Effectiveness of natural substance as preservative agent is needed to be further observed. One of the substances is extract of Glove (Syzygium aromaticum) leaf. This extract was considered to be effective material on Durian (Durio zibethinus) wood preservative against Subterranean termite (Coptotermes sp). The aims of this study were compare the retention and the affectiveness of preservative materials whichÂ extracted from Glove leaf by using different method of extraction. This studi was done at Agro-technology Laboratory of Agricultural Faculty, Tadulako University, over the period of March and June 2014. Bioassay on Termite destruction was done at Maku Village, Dolo of Sigi Regency. The experiment was arranged based on Completely Randomized Design (CRD) in two different factorial patterns. The first factor was different method on leaf extraction (A) i.e. by using ethanol (A1), and by using distillated water (A2). While the second factor (B) was different time on soaking material, i.e. 1 day soaking time (B1), and 3 days were soaking time (B2). All units was performed as negative control. One percent of preservative extract was applied on each experimental unit. The outcome of this study showed that water content of axtract was 14,726% and the density was 0,463 g/cm3. The highest retention value 0,1244 g/cm3 was recorded on the treatment of 3 days ethanol extraction (A1B2), while the lowest value 0,0868 g/cm3 was detected on the treatment of 1 day water extraction. The highest value on effectiveness (or lowest rate on loss weight) 2,4075% was detected after the treatment by using 3 days ethanol extraction substance, while the lowest value 4,6818% wasÂ measured on control unit. Key words: Syzygium aromaticum, Durio zibethinus, Retention, Effectiveness. Â